Prenatal Immune and Endocrine Modulators of Offspring's Brain Development and Cognitive Functions Later in Life - Schepanski, Steven; Buss, Claudia; Hanganu-Opatz, Ileana L.; Arck, Petra C. (Frontiers in Immunology, 2018)
Milestones of brain development in mammals are completed before birth, which provide the prerequisite for cognitive and intellectual performances of the offspring. Prenatal challenges, such as maternal stress experience or infections, have been linked to impaired cognitive devel-opment, poor intellectual performances as well as neurodevelopmental and psychiatric disorders in the offspring later in life. Fetal microglial cells may be the target of such challenges and could be functionally modified by maternal markers. Maternal markers can cross the placenta and reach the fetus, a phenomenon commonly referred to as ‘vertical transfer’. These maternal markers include hormones, such as glucocorticoids, and also maternal immune cells and cyto-kines, all of which can be altered in response to prenatal challenges. Whilst it is difficult to dis-criminate between the maternal or fetal origin of glucocorticoids and cytokines in the offspring, immune cells of maternal origin – although low in frequency - can be clearly set apart from off-spring’s cells in the fetal and adult brain. To date, insights into the functional role of these cells are limited, but it is emergingly recognized that these maternal microchimeric cells may affect fetal brain development, as well as post-natal cognitive performances and behavior. Moreover, the inheritance of vertically transferred cells across generations has been proposed, yielding to the presence of a microchiome in individuals. Hence, it will be one of the scientific challenges in the field of neuroimmunology to identify the functional role of maternal microchimeric cells as well as the brain microchiome. Maternal microchimeric cells, along with hormones and cytokines, may induce epigenetic changes in the fetal brain. Recent data underpin that brain development in response to prenatal stress challenges can be altered across several generations, independent of a genetic predisposition, supporting an epigenetic inheritance. We here discuss how fetal brain development and offspring’s cognitive functions later in life is modulated in the turnstile of pre-natal challenges by introducing novel and recently emerging pathway, involving maternal hor-mones and immune markers.